Hormones, Talent, and Career Unlock Your Hormonal Quotient® - Derval, Diana; Bremer, Johan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The media now regularly feature breakthroughs on the influence of prenatal hormones on the brain and behavior, for instance the link to financial performance or risk management. Based on these findings and their own experiments, the authors present the Hormonal Quotient (HQ) as a scientific, holistic and reliable career management and personal development tool for professionals. Eight HQ profiles and their corresponding typical business skills and preferences are presented and enable the reader to benchmark their HQ with peers, design an ideal career plan, build a winning team in business and find the perfect work-life balance. A complimentary website allows readers to easily measure their HQ online. By the author of "The Right Sensory Mix", Berry-AMA Book Prize Finalist 2011.
Preface -- 1 We Are Our Hormones -- 2 Unlock your Hormonal Quotient R(HQ) -- 3 Find the Right Career Path -- 4 Build a Winning Team -- 5 Find the Perfect Balance -- Conclusion.
Keywords: Economics; Endocrinology; Animal behavior; Educational tests and measurements; Consciousness; Economics/Management Science; Business Strategy/Leadership.; Human Resource Management; Personality and Social Psychology; Behavioural Sciences; Endocrinology; Assessment, Testing and Evaluation